(untitled) (GIST – Education and Learning Research Journal, 2013)
This article is the product of a reflection on two major threats to discourse: the Linguistic Monotony (LM) and the mechanical repetition of grammatical and lexical mistakes. These threats are comprised of different linguistic phenomena that have taken root in our daily communication. The definition and characterization of such phenomena is provided, along with exemplification through authentic texts produced by established national and international mass media. This article seeks not only to make Spanish speakers aware of their repetitive linguistic flaws, but also to convince them regarding the benefits of enhancing discursive skills.